Simulation of Binary CO2/CH4 Mixture Breakthrough Profiles in MIL-53 (Al). (9th December 2015) - Gomez, Luis Fernando; Zacharia, Renju; Bénard, Pierre; Chahine, Richard
Abstract : MIL-53 (Al) aluminum terephthalate, a commercial metal-organic framework, has been studied as a potential candidate for pressure swing adsorption separation of CO2 /CH4 binary mixtures. Pure gas isotherms of CH4 and CO2 measured over 0–6 MPa and at room temperature are fitted with the Dubinin-Astakhov (D-A) model. The D-A model parameters are used in the Doong-Yang Multicomponent adsorption model to predict the binary mixture isotherms. A one-dimensional multicomponent adsorption breakthrough model is then used to perform a parametric study of the effect of adsorbent particle diameter, inlet pressures, feed flow rates, and feed compositions on the breakthrough performance. Commercial MIL-53 with a particle diameter of 20 μ m renders high tortuous flow; therefore it is less effective for separation. More effective separation can be achieved if MIL-53 monoliths of diameters above 200 μ m are used. Faster separation is possible by increasing the feed pressure or if the starting compositions are richer in CO2 . More CH4 is produced per cycle at higher feed pressures, but the shortened time at higher pressures can result in the reduction of the CH4 purity.